Ecological diagnosis of Lake Batur (Bali, Indonesia) post-disturbance using multimetric phytoplankton indices - SANG AYU MADE PUTRI SURYANI; I GEDE SUDIARTA; NI MADE DARMADI; DEWA GEDE SEMARA EDI; I KETUT SUDIARTA; GEDE AGUS SURYA PRATAMA; I MADE ABDI JANAGUNA; I PUTU SUGIANA (Society for Indonesian Biodiversity, 2025)
Abstract. Suryani SAMP, Sudiarta IG, Darmadi NM, Edi DGS, Sudiarta IK, Pratama GAS, Janaguna IMA, Sugiana IP. 2025. Ecological diagnosis of Lake Batur (Bali, Indonesia) post-disturbance using multimetric phytoplankton indices. Biodiversitas 26: 4982-4990. Plankton communities are rapid responders to environmental change and serve as sensitive indicators of ecological stress in tropical volcanic lakes. In July 2025, Lake Batur (Bali, Indonesia) experienced a major fish mortality linked to hypolimnetic upwelling and nutrient enrichment from aquaculture. To assess post-disturbance conditions, we sampled three sites with varying aquaculture intensity—Seked (low), Buahan (moderate), and Trunyan (high, mortality epicenter)—one week after the event. Field measurements included temperature, pH, dissolved oxygen, conductivity, redox potential, nutrients, and sulfide, while phytoplankton analysis covered diversity (Shannon–Wiener), evenness (Pielou), dominance (Simpson), and saprobity (Dahuri). Results revealed clear spatial contrasts. Trunyan showed the strongest stress signals, with oxygen depletion, negative redox potential, and elevated ammonia, while Seked and Buahan displayed milder alterations. In total, 23 phytoplankton genera were identified, dominated by diatoms such as Ulnaria and Actinotaenium. Trunyan exhibited reduced richness, lower diversity (H’ = 1.84), and higher dominance (D = 0.27), indicating a shift toward opportunistic taxa. Saprobity values showed a gradient of organic pollution, increasing from Seked (1.5) to Trunyan (2.0), consistent with aquaculture intensity. These findings highlight the value of integrating multimetric plankton indices with physicochemical data to distinguish natural upwelling effects from anthropogenic nutrient loading. While diatom persistence suggests some resilience, recovery of sensitive taxa depends on reducing nutrient inputs and regulating aquaculture. This integrative framework offers a practical diagnostic tool for adaptive lake management and contributes to achieving clean water, climate action, and aquatic biodiversity goals.